2014
DOI: 10.15835/buasvmcn-hort:10411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fertilization on Yield and Quality of Biomass of Quinoa (Chenopodium quinoa Willd.) and Green Amaranth (Amaranthus retroflexus L.)

Abstract: The effect of organic and inorganic fertilization on yield and biomass quality of two species: quinoa (Chenopodium quinoa Willd.) and green amaranth (Amaranthus retro lexus L.) was studied in this paper. The agronomic performance and nutritional value of quinoa and green amaranth was analyzed in order to establish them as alternatives to local forages for dry-season feeding of ruminants in the Mediterranean region. The experiment was laid out in a split-plot design with two replicates, two main plots (quinoa a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
2
10
0
1
Order By: Relevance
“…reacted the same way. This is also pointed out by Efthimiadoua et al (2012) and Papastylianou et al (2014). Opposite to this case, fertilizers can reduce crop weediness.…”
Section: Results and Discussion Floristic Composition And Taxonomic Ssupporting
confidence: 52%
“…reacted the same way. This is also pointed out by Efthimiadoua et al (2012) and Papastylianou et al (2014). Opposite to this case, fertilizers can reduce crop weediness.…”
Section: Results and Discussion Floristic Composition And Taxonomic Ssupporting
confidence: 52%
“…In this study, crude protein accounted for only 11.21% of the dry weight of the green forage. Papastylianou et al (2014) also reported crude protein levels of 11.1 -14.7% DM in green matter from this plant. In the samples of quinoa green forage analysed in this study, the concentrations of crude ash, crude fat, crude fibre and nitrogen-free extract were higher than those reported by Gęsiński (2012).…”
Section: Resultsmentioning
confidence: 62%
“…Owing to the valuable properties of quinoa, its unusual resistance and ecological plasticity, and its high nutritional value, the Food and Agriculture Organization (FAO) declared the year 2013 the 'International Year of Quinoa' (Kakabouki et al, 2014;Papastylianou et al, 2014). Quinoa has a long growing season and even European varieties do not mature in Poland until late September (Gęsiński, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Vermicompost has been advocated as good organic manure for use in integrated management practices in field crops. Vermicompost not only increases organic carbon status of the soils but also increases soil water holding capacity, flocculation of soil and availability of nutrients and thus improves soil and crop production sustainability [21] In addition, fertilization with compost showed higher values in most quality traits of biomass in quinoa crop other than synthetic fertilizers [22]. In comparing the effect of compost and vermicompost on Amaranthus viridis production; Islam et al [23] found that vermicompost application gave higher result for growth, yield indices and nutrient content than the conventional aerobic compost.…”
Section: Introductionmentioning
confidence: 99%